STRATEGI OMBUDSMAN REPUBLIK INDONESIA (ORI) PERWAKILAN PROVINSI BALI DALAM MENEKAN MALADMINISTRASI PELAYANAN PUBLIK (Studi Kasus: Kota Denpasar) - Ardani, Ni Luh Widya; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
Lembaga Ombudsman Republik Indonesia Perwakilan Provinsi Bali is an institution that has overseeing the implementation of public services. The purpose of this research was to determine the strategies in preventing maladministration of public services. This research is descriptive qualitative with observation, interviews, and documentation. The results of the analysis based on the process model of the strategic management stages according to Wheelen and Hunger and the SWOT analysis show that the Ombudsman Perwakilan Bali did not carry out an environmental analysis because strategy was based on the POK Ombudsman Republik Indonesia. The formulation process did not involve the community too. The good thing is, in 2020, the strategy implementation and evaluation and control processes have been carried out according to the performance plan. Based on the results, there are alternative strategies as further optimization looking at the WT (Weakness-Treaths) strategy. Keywords: Ombudsman strategy, maladministration, public service.